CXCR3-deficient mesenchymal stem cells fail to infiltrate into the nephritic kidney and do not ameliorate lupus symptoms in MRL.Faslpr mice. (October 2018) - Lee, J H; Lee, H K; Kim, H S; Kim, JS; Ji, A Y; Lee, J S; Kim, K S; Lee, T Y; Bae, S C; Kim, Y; Hong, J T; Han, S B
Mesenchymal stem cell therapy is a promising candidate for the treatment of systemic lupus erythematosus (SLE). To exert their efficacy fully, mesenchymal stem cells must infiltrate efficiently into the lesion sites. Here, we examined the role of CXCR3 in mesenchymal stem cell infiltration into the kidney of MRL. Fas lpr mice, which highly expressed CXCL10. The phenotypes, production of immunosuppressive mediators, and capacity to inhibit T and B cells of CXCR3-deficient mesenchymal stem cells were similar to those of wild-type mesenchymal stem cells. However, they showed less infiltration into the nephritic kidney, less conjugation with endothelial cells and weaker MMP-9 expression than did wild-type mesenchymal stem cells. Consequently, CXCR3-deficient mesenchymal stem cells did not ameliorate lupus symptoms in MRL. Fas lpr mice in comparison with wild-type mesenchymal stem cells. In summary, our data suggest that upregulation of CXCR3 in mesenchymal stem cells will be a good strategy to increase their infiltration into the kidney, which will improve therapeutic outcomes in SLE.